Cooling tower Legionella pneumophila surveillance results: Vancouver, Canada, 2021. (28th February 2023) - Radziminski, Christopher; White, Phillip
Abstract: Cooling towers have been linked to Legionnaires' disease cases and outbreaks. Legionella pneumophila results (from a culture-based method) are presented for 557 cooling towers across the City of Vancouver, Canada for 2021. Results of 10 CFU/mL or greater (defined as exceedances) were reported for 30 cooling towers (5.4%), including six >1, 000 CFU/mL, and L. pneumophila serogroup 1 (sg1) was identified in 17 of these cooling towers (out of 28 with serogroup-level analysis). The data indicate highly localised Legionella issues, with exceedances concentrated within 16 facilities, including two hospitals. In the 3 months preceding each cooling tower exceedance, the nearest municipal water sampling station had a free chlorine residual of at least 0.46 mg/L and a temperature of <20 °C. There was not a statistically significant correlation between the L. pneumophila concentration of a cooling tower in exceedance and the municipal water free chlorine residual, temperature, pH, turbidity or conductivity. There was a statistically significant negative correlation between the concentrations of L. pneumophila sg1 and other L. pneumophila serogroups in cooling towers. This unique dataset underscores the pivotal role of building owners and managers in preventing the growth of Legionella bacteria and the value of regulations to verify operations and maintenance practices. HIGHLIGHTS: In 2021, water samples from about 1-in-20 cooling towers in the City of Vancouver reported Legionella pneumophila concentrations of 10 CFU/mL or greater (defined as exceedances), including at two hospitals. The data point to building-scale Legionella issues. In cooling towers reporting exceedances, there was not a statistically significant correlation between conventional municipal water quality parameters and L. pneumophila concentration. There was a statistically significant negative correlation between the concentrations of L. pneumophila serogroup 1 and 'non-serogroup 1' L. pneumophila in cooling towers, hinting at a potentially competitive relationship.